A case of myopic strabismus fixus “Fixed” with loop myopexy - Sanitha Sathyan; R Jyothi (Kerala Journal of Ophthalmology, 2016)
Myopic strabismus fixus is a rare condition seen in high myopes and presents with sudden onset of strabismus. This case report describes a high myopic patient who presented with acute onset strabismus and was successfully treated with loop myopexy of superior rectus and lateral rectus muscles.